Relationship between Chloroplast Development and ent-Kaurene Biosynthesis in Peas - Choinski, John S. (1980)
Treatment of etiolated pea (Pisum sativum (L. cv. Alaska) seedlings with 2′-isopropyl-4′-(trimethylammonium chloride)-5′-methylphenyl piperidine-1-carboxylate (Amo-1618) prior to irradiation with white light inhibits photomorphogenesis and formation and stacking of thylakoid membranes in the chloroplasts, as well as (−)-kaur-16-ene (ent-kaurene)biosynthesis. Exogenous gibberellic acid also inhibits greening. A crudely determined action spectrum for the photoinduction of ent-kaurene biosynthesis shows two peaks, one in the blue region at 458 to 490 nanometers and another in the red region at 606 to 678 nanometers. The possible participation of phytochrome in the photoinduction of ent-kaurene biosynthesis is indicated by comparative effects of red, far red, and alternating red/far red irradiations on enhancement of enzyme activity. The activity of blue light as well as red shows a similarity of the photoinduction of ent-kaurene synthesis activity to the high irradiance responses, and indicates probable participation of a second photoreceptor. From these observations, it is concluded that photoinduction of ent-kaurene biosynthesis and chloroplast development in shoots are closely linked processes.